Introducing 6G technology to support metaverse for telecommunication engineering students in Universitas Pendidikan Indonesia - Endah Setyowati; Syifaul Fuada; Khoirul Anwar; Muhamad Dzikri Danuarteu; Salwa Tasya Fathira Purba; Anggie Wijaya (Universitas Muhammadiyah Magelang, 2023)
Research on 6G have been started with many applications including on the support of Metaverse, where humans can interact in cyberspace with real experiences. To introduce and provide an understanding of this technology, Program Studi Sistem Telekomunikasi Universitas Pendidikan Indonesia kampus Purwakarta held a Studium Generalle with the theme of